Data on variability in k600 and CO2/CH4 emissions within and across streams of different stream order - Wallin, Marcus (Uppsala University, 2018)
The study based to this dataset explored the variability in k600 and subsequent CO2 and CH4 emission rates within and across streams of different stream order (SO). We conducted, for the first time in streams, direct turbulence measurements using an acoustic Doppler velocimeter (ADV) to determine the spatial variability in k600 across a variety of scales with a consistent methodology.

This study was conducted in an ∼80 km2 fourth-order catchment in south-central Sweden (; 59.803279°N, 15.167283°E). The catchment consists of 84.3% forest; 10% wetlands, marshes, fens and bogs; 5.1% lakes; 0.5% agriculture; and 0.06% habitation. The sampled sites were distributed along a hydrological chain of streams and lakes with streams ranging from SO1 to SO4. The average transect water velocity was multiplied by the cross-section area to obtain an average Q for the stream reach. Water temperature, electrical conductivity, and dissolved oxygen were measured in situ with an HQ40d Portable Multiparameter Meter (HACH), and pH was measured in the lab from water samples on a Metrohm 744 pH meter. We conducted sampling campaigns on 3 occasions: August 2015, April 2016, and June 2016.

For further information about data and data collection, see "High spatial variability of gas transfer velocity in streams revealed by turbulence measurements" by Kokic et al (2018).

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av denna katalogpost för informaiton om data och insamling.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data on variability in k600 and CO2/CH4 emissions within and across streams of different stream order
ADV.k600.CO2.CH4
Keywords: inland waters; inlandsvatten; carbon dioxide; koldioxid; methane; metan; gases; gaser; velocity; hastighet; Environmental Sciences; Miljövetenskap